2021
DOI: 10.3390/jcm10153428
|View full text |Cite
|
Sign up to set email alerts
|

Control of Glucose, Blood Pressure, and Cholesterol among Adults with Diabetes: The Brazilian National Health Survey

Abstract: ABC (glucose, blood pressure and LDL-cholesterol) goals are basic standards of diabetes care. We aimed to assess ABC control and related factors in a representative sample of Brazilian adults with diabetes. We analyzed 465 adults with known diabetes in the Brazilian National Health Survey. The targets used were <7% for glycated hemoglobin (A1C); <140/90 mmHg for blood pressure; and <100 mg/dL for LDL-C, with stricter targets for the latter two for those with high cardiovascular (CVD) risk. Individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
2
11
1
1
Order By: Relevance
“…In Brazil, the smoking prevalence has been declined from 35% in 1990 to 11.3% in 2017 27 29 . The diabetes prevalence reduced 30% for men and 26% for women from 1990 to 2017 30 . This rising pancreatic cancer mortality trend of may be associated with an unknown risk factor, since there are differences in prevalence of risk factors between Brazilian regions [28][29][30][31][32] , this could be the reason in disparities of the mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the smoking prevalence has been declined from 35% in 1990 to 11.3% in 2017 27 29 . The diabetes prevalence reduced 30% for men and 26% for women from 1990 to 2017 30 . This rising pancreatic cancer mortality trend of may be associated with an unknown risk factor, since there are differences in prevalence of risk factors between Brazilian regions [28][29][30][31][32] , this could be the reason in disparities of the mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrating the control of multiple risk factors in diabetes are scarce in low-and middle-income countries. Based on a small subsample of a probabilistic national Brazilian survey, we demonstrated that target achievement is usually poor, except for non-smoking [6]. However, that study lacked statistical power to assess the factors related to ABC control.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, 34% had HbA 1c levels above 8%. These figures, and those regarding the control of other risk factors, indicate that much more is needed in diabetes mellitus management in Brazil 8 . In addition to privately financed care, Brazil has a universal health system (Sistema Único de Saúde), with a public primary care network available to all and covering 63% of the population in 2021.…”
mentioning
confidence: 99%